A Systematic Review on Clinimetric Properties of Play Instruments for Occupational Therapy Practice - Muhammad Hibatullah Romli; Farahiyah Wan Yunus (Occupational Therapy International)
Play is considered the main occupation for children. Pediatric occupational therapists utilize play either for evaluation or intervention purpose. However, play is not properly measured by occupational therapists, and the use of play instrument is limited. This systematic review was aimed at identifying play instruments relevant to occupational therapy practice and its clinimetric properties. A systematic search was conducted on six databases (Academic Search Complete, CINAHL, MEDLINE, Psychology and Behavioral Science Collection, Scopus, and ASEAN Citation Index) in January 2020. The quality of the included studies was evaluated using Law and MacDermid’s Appraisal for Clinical Measurement Research Reports, and psychometric properties of play instruments were evaluated using Terwee’s checklist while the clinical utility is extracted from each instrument. Initial search identifies 1,098 articles, and only 30 articles were included in the final analysis, extracting 8 play instruments. These instruments were predominantly practiced in the Western culture, which consists of several psychometric evidences. The Revised Knox Preschool Play Scale is considered the most extensive and comprehensive play instrument for extrinsic aspect, whereas the Test of Playfulness + Test of Environmental Supportiveness Unifying Measure is a promising play instrument for intrinsic aspect on play, where both instruments utilize observation. My Child’s Play is a potential questionnaire-based play instrument. However, the current development of play instruments in the occupational therapy field is immature and constantly evolving, and occupational therapists should exercise good clinical reasoning when selecting a play instrument to use in practice.